Parameters of effects in decision making of automotive assembly line using the Analytical Hierarchy Process method - Nelfiyanti, Nelfiyanti; Nik Mohd Zuki, Nik Mohamad; MFF, Ab. Rashid; Anwar Ilmar, Ramadhan (Elsevier, 2022)
The automotive industry contributes high income to most of the countries. The assembly line is an essential part of the automotive industry because it combines all the components into a complete body unit. Assembly lines often experience delays in meeting production targets, requiring overtime to complete. Musculoskeletal Disorder (MSD) complaints among assembly workers predominantly lie in trimming, chassis, and finishing processes. Improvements are needed to reduce complaints according to the priority process. This study aims to prioritize the process on the assembly line with the parameters of work position, workload, work layout and equipment. This study implements the Analytical Hierarchy Process (AHP) method to achieve the objectives of the decision-making process. Preliminary weighting priorities for chassis, finishing and trimming are 0.6153, 0.2313 and 0.1533; respectively highest weight is in the chassis process and will be a priority for this study in optimizing solutions.